PENGARUH FASILITAS DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR KONSENTRASI MANAJEMEN PERKANTORAN - Erica Puspita Maharani; Brillian Rosy (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The research carried out aims to determine the influence that learning facilities and learning independence have on learning outcomes in the Office Management Concentration subject located at SMKN 10 Surabaya. This research uses a quantitative approach method. The population of this research was all students in class. Next, the researcher carried out data analysis using the multiple regression method, resulting in research results in the form of (1) There is a significant influence on learning facilities on partial learning outcomes, (2) There is a significant influence on learning independence on partial learning outcomes, (3) There is a significant influence on learning facilities and learning independence on learning outcomes simultaneously.